Pendampingan Rohani Islam melalui Kegiatan Maulid Nabi Muhammad SAW sebagai Implementasi Bakat Siswa di SMKN 3 Palangka Raya - Meylinda Agustina; Muhammad Redha Anshari; Ana Kameloh Dian (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The Maulid Nabi Muhammad Saw activity at SMKN 3 Palangka Raya is held as a form of Islamic spiritual assistance, as well as a place to develop students' talents in a religious context. This activity involves various activities such as lectures, Islamic art, and creative presentations related to the Prophet's life story, with the aim of strengthening students' love for the Prophet Muhammad and supporting the development of speaking, art, and cooperation skills. This article discusses the implementation of this mentoring activity, the impact felt by students, and the successful implementation of student talents. Using a Participatory Action Research (PAR) approach, this activity showed an improvement in the aspects of spirituality, speaking skills, and talent development. The mentoring results show that students are not only more involved in religious activities, but also more confident in expressing their religious understanding. This activity creates a positive atmosphere that supports students to learn, create, and contribute to spiritual and social development.